(untitled) (Jurnal Riset Manajemen Akuntansi Indonesia, 2024)
This study aims to determine the performance of the Yogyakarta Police Satlantas Regident Unit personnel and the factors that cause less than optimal performance of the personnel so that it can be seen efforts to improve the performance of Yogyakarta Police Satlantas Regident Unit personnel. The existence of the Yogyakarta Police Satlantas regident unit is very much needed by the community to support the smoothness of making a Driving License (SIM), therefore the personnel of the Yogyakarta Police Satlantas Regident unit need to evaluate what public services are still constrained in public services, especially in the service of submitting a Permit. Driving (SIM) is increasing.This study uses a qualitative method. Qualitative data is used to determine the factors that cause personnel performance is not optimal and efforts to improve personnel performance. Data were collected by literature study, observation, and interviews. Factors that cause personnel performance to be less than optimal because the number of personnel with applicants is not comparable, photo camera facilities are few so that queues pile up at photo sessions, lack of public literacy on the information provided. Efforts are being made to overcome these problems, namely by providing information facilities, online queuing systems, mobile SIM services through the innovation of SIM MAMI and SIMON PALACE services.